Anniversary Emblem & Logotype Designs - Okur, Çağlar (Journal of Education Culture and Society, 2020)
Corporate anniversaries are mostly used as a promotional event to increase the value of corporate identity of firms, business enterprises or their brands. They are also used to create investment trust or strengthen the relations between, employees and customers. What makes corporate anniversaries meaningful is the importance of their moral value of continuity. Signs that are designed to identify these moral values and indicate the anniversaries can be defined as “anniversary emblems.” The design and uniqueness of these emblems are important in the means of being remarkable and memorable. Thus creative and unique results can be achieved by converting the numbers of anniversaries into expressive signs. This article focuses on existing design approaches and examples of anniversary emblem designs.